BENEFITS OF ADAPTATION OF PEOPLE - UNDER HYPERTENSIVE DRUG THERAPY - IN THE WATER IN HORIZONTAL POSITION (Fiep Bulletin - online, 2012)
Based on the literature on this topic, it is observed that most studies associate the benefits of antihypertensive drugs only to the practice of aquatic exercise in an upright position, and few use the horizontal position as a basis for treatment. Thus, the current study aimed to analyze the adaptation of hypertensive reactions to the aquatic environment, by learning survival swimming (dog) and backstroke. Nine individuals participated on this program, aged between 56 to 75 years diagnosed with mild hypertension, no history of water activities and without interruption of drug therapy during the program. The study lasted 8 weeks, totaling 16 sessions, each session was of 50 minutes, held twice a week. Each session consisted of four stages: 1 - Blood pressure (BP) and heart rate (HR) taken after five minutes of initial rest. 2 - taking BP and HR in supine floating after two minutes of rest. 3 - taking BP and HR after doing the exercises related to swimming and 4 - taking BP and HR after five minutes, in final resting. The initial averages BP and HR - related to moment one - of each individual were carried out one week before the program on two different days, adding up to a third pressure taking carried out on the first day of the program, generating an average pre-study. Comparing the averages of SBP (Systolic Blood Pressure) and DBP (Diastolic Blood Pressure) of each individual pre-study of initial rest, with the final at the same time post-study, there were significant reductions of 11 mmHg on SBP average and 6 mmHg on diastolic average. We conclude that after the analysis of the results, the study showed benefits for the sample studied by the observation of reduced levels of blood pressure after exercise.
Keywords: Swimming; hypertension; horizontal position